Comparative Study between Monopolar Electrodes and Bipolar Electrodes in Hysteroscopic Surgery - Tammam, Abdelaziz Ezzeldin (J Clin Diagn Res, 2015)
BACKGROUND: The hysteroscopic surgery has become a simple and safe technique, with the use of small hysteroscopes and bipolar energy with trained surgeons, which can prevent abortions and probably increase fertility. AIM: The study was conducted to evaluate the outcomes after hysteroscopic surgery by using uninopolar or bipolar electrodes. SETTING AND DESIGN: At the department of Obstetrics and Gynaecology, Qena university hospital and is a prospective non randomized clinical study. MATERIALS AND METHODS: One hundred fifty patients who included in this study were non randomly classified into two groups; one for hysteroscopic surgery by using bipolar electrode and the second group using unipolar electrode. Operative complications; bleeding, perforation, fluid over load and hyponatraemia were recorded. Also, operative time and hospital stay were included. RESULTS: There were no statistically significant differences between both groups in patient’s characteristics, ultrasono-graphic findings, serum sodium levels before surgical interference, perforation and intraoperative bleeding. The fluid overload was significantly higher in unipolar group (p value= 0.03), postoperative hyponatraemia was significantly marked in unipolar group (p<0.05) and the changes of the levels of serum sodium in unipolar group in comparison to bipolar group were significantly different (p = 0.01). The mean operative time was significantly less in the bipolar group when compared to the unipolar group (p = 0.01) and the hospital stay was obviously less for patients of the bipolar group in comparison to unipolar group (p=0.04). CONCLUSION: Operative hysteroscopy using bipolar electrodes associated with significant decrease in hyponatraemia, operative time and postoperative hospital stay. So, it is safe and effective method when compared to using the unipolar electrodes.